Intracellular persistence of Staphylococcus aureus in endothelial cells is promoted by the absence of phenol-soluble modulins. Issue 1 (1st January 2021) - Siegmund, Anke; Afzal, Muhammad Awais; Tetzlaff, Felix; Keinhörster, Daniela; Gratani, Fabio; Paprotka, Kerstin; Westermann, Martin; Nietzsche, Sandor; Wolz, Christiane; Fraunholz, Martin; A. Hübner, Christian; Löffler, Bettina; et al.
ABSTRACT: A large proportion of clinical S. aureus isolates that carry an inactive Agr system are associated with persistent infection that is difficult to treat. Once S. aureus is inside the bloodstream, it can cross the endothelial barrier and invade almost every organ in the human body. Endothelial cells can either be lysed by this pathogen or they serve as a niche for its intracellular long-term survival. Following phagocytosis, several vesicles such as phagosomes and autophagosomes, target intracellular S. aureus for elimination. S. aureus can escape from these vesicles into the host cytoplasm through the activation of phenol-soluble modulins (PSMs) αβ. Thereafter, it replicates and lyses the host cell to disseminate to adjacent tissues. Herein we demonstrate that staphylococcal strains which lack the expression of PSMs employ an alternative pathway to better persist within endothelial cells. The intracellular survival of S. aureus is associated with the co-localization of the autophagy marker LC3. In cell culture infection models, we found that the absence of psmαβ decreased the host cell lysis and increased staphylococcal long-term survival. This study explains the positive selection of agr -negative strains that lack the expression of psmαβ in chronic infection due to their advantage in surviving and evading the clearance system of the host.